• 4a^2-4ab+b^2:4a^2-b^2 при а =1:11 b=-9:11​

Ответы 2

  • 4а²-4ав+в²/4а²-в²=(2а-в)²/(2а-в)(2а+в)=2а-в/2а+в

    подставляем значения

    2/11-9/11  / 2/11+9/11=-7/11

  •  \frac{ {(2x - y)}^{2} }{(2x - y)(2x + y)}  =  \frac{2x - y}{2x + y}  \frac{ \frac{2}{11} +  \frac{9}{11}  }{ \frac{2}{11}  -  \frac{9}{11} }  =  -  \frac{11}{7}
    • Автор:

      arynvrs3
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years